The Year 2004: Historiographical Issues Concerning Islam in The Netherlands - Berger, Maurits (Journal of Muslims in Europe, 2023)
This article aims to take a new approach to the study of Islam in Europe today by adopting a historiographical method with particular emphasis on the concept of temporality. The case-study will be The Netherlands, where it will be shown that a convergence of events in the year 2004 has contributed to the shaping of the national experience of ‘Islam’. It will be argued that these events, and the manner in which they took place, have created a national traumatic experience that has fossilised the way the Dutch have talked and thought about Islam since then.